2022
DOI: 10.1155/2022/8956850
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization and Evaluation of an Intelligent Short-Term Blood Glucose Prediction Model Based on Noninvasive Monitoring and Deep Learning Techniques

Abstract: Continuous noninvasive blood glucose monitoring and estimation management by using photoplethysmography (PPG) technology always have a series of problems, such as substantial time variability, inaccuracy, and complex nonlinearity. This paper proposes a blood glucose (BG) prediction model for more precise prediction based on BG series decomposition by complete aggregation empirical mode decomposition based on adaptive white noise (CEEMDAN) and the gated recurrent unit (GRU) that is optimized by improved bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The above-mentioned operations are repeated until there is no maximum or minmum value in the residue signal ๐‘Ÿ ๐‘›+1 (๐‘ก) [24]. The final decomposition level (๐‘) is ๐‘› + 1, and the final residue signal is ๐‘Ÿ ๐‘ (๐‘ก).…”
Section: Ceemdan Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned operations are repeated until there is no maximum or minmum value in the residue signal ๐‘Ÿ ๐‘›+1 (๐‘ก) [24]. The final decomposition level (๐‘) is ๐‘› + 1, and the final residue signal is ๐‘Ÿ ๐‘ (๐‘ก).…”
Section: Ceemdan Principlementioning
confidence: 99%
“…EMD based methods are more elastic than WT and adaptive filtering, but for the discontinuous signal EMD decomposition can lead to modal aliasing. Aiming at this problem, some modified EMD methods are contributed by adding Gaussian white noise to the signal, such as ensemble EMD (EEMD) [21,22], complementary EEMD (CEEMD) [23] and complete EEMD with adaptive noise (CEEMDAN) [24,25]. EEMD and CEEMD directly add noise to the original signal, which can solve the problem of modal aliasing, but the added noise may affect the decomposed signal and produce the problem of noise residue, with a result of mutated reconstruction signal.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing average value [16,17], linear interpolation [17,18], KNN [19,20] Dimensionality reduction PCA [8], pooling layer [21], t-SNE [22], SPCA [23] Removing outliers Pauta criterion [18], EWMA [24] Feature selection PSO [1], LASSO [8,25], ASO [26], GA [27], MI [28], GRA [29], PCC [30], CCA [31] Decomposition EMD [32], EEMD [33], CEEMDAN [19,27,[34][35][36][37][38], ICEEMDAN [39], SSA [40,41], VMD [42], SVMD [43] Normalization [6,17,20,27,30,31,34,42,[44][45][46][47][48][49]…”
Section: Missing Valuesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%